2011
DOI: 10.1037/a0022029
|View full text |Cite
|
Sign up to set email alerts
|

Binocular rivalry: A window into emotional processing in aging.

Abstract: Previous binocular rivalry studies with younger adults have shown that emotional stimuli dominate perception over neutral stimuli. Here we investigated the effects of age on patterns of emotional dominance during binocular rivalry. Participants performed a face/house rivalry task where the emotion of the face (happy, angry, neutral) and orientation (upright, inverted) of the face and house stimuli were varied systematically. Age differences were found with younger adults showing a general emotionality effect (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 70 publications
6
11
0
Order By: Relevance
“…These results might be due to different emotion regulation strategies employed by younger and older adults. Older adults are more likely than younger adults to ignore negative stimuli, while enhancing attention to and processing of positive stimuli (Bannerman, Regener, & Sahraie, 2011; Emery & Hess, 2011). In contrast, compared with older adults, younger adults are better at reappraising negative emotional stimuli to reduce their emotional impact (Opitz, Rauch, Terry, & Urry, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results might be due to different emotion regulation strategies employed by younger and older adults. Older adults are more likely than younger adults to ignore negative stimuli, while enhancing attention to and processing of positive stimuli (Bannerman, Regener, & Sahraie, 2011; Emery & Hess, 2011). In contrast, compared with older adults, younger adults are better at reappraising negative emotional stimuli to reduce their emotional impact (Opitz, Rauch, Terry, & Urry, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This in turn has been argued to result in increased attention to, and memory for, positive information, and/or avoidance of negative information (for a review see Mather & Carstensen, 2005). Although older adults' positivity can sometimes be witnessed under conditions of limited cognitive control (e.g., Allard & Isaacowitz, 2008;Bannerman et al, 2011), it is thought mainly to reflect a consciously controlled preference (Mather & Carstensen, 2005), and thus, would be expected to occur primarily in response to supraliminal rather than subliminal cues.…”
Section: Discussionmentioning
confidence: 99%
“…A study examining age differences in binocular rivalry effects for emotional faces also revealed that older adults suppress processing of angry faces and enhance processing of happy faces. 59 In this study, a picture of a house was presented to one eye and a picture of a face was presented to the participant's other eye on each trial. Under these conditions, people perceive the two images alternating, as they compete in the brain for perceptual dominance.…”
Section: Downregulating Negative Affect May Be More Of a Default Modementioning
confidence: 99%